Harnessing the Potentials of the Ghanaian Diaspora: An Analysis of Ghana’s Engagement with Its Diaspora - Adjei, E. (University Of Ghana, 2018)
The study examined how Ghana could harness its the potentials of is Diaspora to complement its development efforts. One of the biggest diasporas in recent times is that of the African diaspora or more specifically the Sub-Saharan diaspora. It used both primary and secondary sources to review, since independence, how successive governments have exploited the potentials of Ghana’s rich Diaspora in their development agenda. It uncovered that the diaspora constitutes one of the most reliable sources of Foreign Direct Investment (FDI), entrepreneurs, specialised human resources, ethics and concepts of best practices, philanthropists, foreign currency remittances and agents of technology transfer. Ghana’s engagement of the Diaspora to complement its development was intensified in the 1980s and l990s when Ghana’s economic fortunes declined, and ERP and SAP were instituted. The advent of multi-party politics from the l990s upped Ghana’s Diaspora engagement through policy instruments such as reinvention Pan-Africanism, dual-citizenship, Diaspora Home-Coming festivals, Non-Resident Ghanaian Secretariat for Investment, the Joseph Project, creation of Tourism and Diaspora Relations Ministry, the Diaspora Support Unit, and the Constitutional Review Commission (CRC) for Diaspora Engagement. These Diaspora engagement policies were, however, largely ad hoc strategies that lost their significance with change of governments. The study emphasized the need for a more coherent and comprehensive Diaspora engagement national policy that involves all sectors of the Ghanaian society. It recommended that future Diaspora policies formulations must involve the Diaspora, creation of a robust Diaspora database, and a proactive redressal of the Diaspora’s needs and challenges abroad for a better harnessing of the Diaspora’s development potentials to Ghana.
MA.
Keywords: Ghanaian Diaspora